Islamic Mindfulness to Enhance Self-Regulation and Academic Success in Generation Z - Norman, Efrita; Windi Megayanti; Arman Paramansyah; Firda Dwi Rahmawati (Medina-te : Jurnal Studi Islam, 2025)
The rapid advancement of digital technologies has significantly impacted Generation Z, particularly in relation to self-regulation and academic performance. This generation faces challenges in managing stress, attention, and emotions, often exacerbated by the overuse of social media and digital devices. The aim of this study was to explore the potential of Islamic mindfulness, incorporating practices such as dhikr and tafakur, in improving self-regulation and academic performance among high school students in Indonesia. This quasi-experimental research utilized a pretest-posttest control group design, involving 300 students from six high schools in Bogor. The experimental group received an 8-week intervention focusing on Islamic mindfulness techniques, while the control group continued their regular academic activities. Self-regulation and academic performance were measured using standardized questionnaires and academic tests before and after the intervention. The results revealed that students in the experimental group showed significant improvements in both self-regulation and academic performance, in contrast to the control group. This study contributes to the field of Islamic education by providing evidence for the effectiveness of Islamic mindfulness in fostering better emotional regulation, focus, and academic outcomes in the digital age. It offers practical solutions for integrating mindfulness into the educational curriculum, supporting the mental well-being and academic success of Generation Z students in Islamic educational settings.